Fodor's 2009 U.S. & British Virgin Islands. - Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to the U.S. and British Virgin Islands, with maps and information on accommodations and restaurants, shopping and entertainment, and interesting tourist sites.
Cover title: U.S. & British Virgin Islands 2009.
Maps on inside cover.
Includes bibliographical references and index.
Young Adult
Keywords: British Virgin Islands -- Guidebooks; Virgin Islands of the United States -- Guidebooks; British Virgin Islands -- Guidebooks; Virgin Islands of the United States -- Guidebooks